The Body and the Corporeal in the Conception of Ibn Sina (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
We try, through this research, to focus on a basic and important issue, which is the body and the corporeal according to Ibn Sina, where we deal with the body with what is the body according to Ibn Sina, in a detailed and accurate manner, and we try to show whether the body with him is the long, wide and deep body, or the body is the body In which these three dimensions are imposed as an assumption and not as existing in it,and we try to show Ibn Sina's position on the principles that make up the body (matter and image) , and what is the relationship that connects matter with the image, is it the relationship of addition or the relationship of existential correlates, and which of them constitutes a cause for the other, matter or The image, and whichever one precedes the other in existence